Front-line service providers' appraisal of Saskatchewan's HIV services and strategy: A qualitative study. Issue 2 (3rd April 2018) - Sami, Maleeha; Maposa, Sithokozile; Exner-Pirot, Heather; Anonson, June
ABSTRACT: This qualitative study examined front-line health care providers' understandings of the Saskatchewan Ministry of Health's 2010–2014 HIV strategy, their capacity building needs, and perspectives on how well they were implementing HIV services. Providers' experiences of engaging people living with HIV, community leaders, and communities affected by the epidemic reveal a need to strengthen interprofessional networks. Our findings also indicate the need for HIV services to respond to coexisting challenges, including substance use, violence, and mental health care for people living with HIV. Programs in rural northern Saskatchewan should also address homelessness, disparities in access to care, and HIV stigma issues.